An assessment of polyurethane foam passive samplers for atmospheric metals compared with active samplers. (May 2018) - Li, Qilu; Yang, Kong; Li, Jun; Zeng, Xiangying; Yu, Zhiqiang; Zhang, Gan
Abstract: In this study, we conducted an assessment of polyurethane foam (PUF) passive sampling for metals combining active sampling. Remarkably, we found that the metals collected in the passive samples differed greatly from those collected in active samples. By composition, Cu and Ni accounted for significantly higher proportions in passive samples than in active samples, leading to significantly higher uptake rates of Cu and Ni. In assessing seasonal variation, metals in passive samples had higher concentrations in summer (excluding Heshan), which differed greatly from the pattern of active samples (winter > summer), indicating that the uptake rates of most metals were higher in summer than in winter. Overall, due to the stable passive uptake rates, we considered that PUF passive samplers can be applied to collect atmospheric metals. Additionally, we created a snapshot of the metal pollution in the Pearl River Delta using principal component analysis of PUF samples and their source apportionment. Graphical abstract: Image 1 Highlights: Atmospheric metals were collected by polyurethane foam passive samplers and active samplers. Passive samples and active samples showed great differences for composition. Cu and Ni had extremely high passive uptake rates. Most of metals had higher passive uptake rates in summer.